Characteristics and Economic Achievements of Coffee Farmers as Community Forest (HKM) in The Bukit Dingin Forest Protected Areas, Pagaralam City - Rahmat Kurniawan; Fachrurrozie Sjarkowi; Mirza Antoni; Yunita (Journal of Global Sustainable Agriculture, 2025)
The community in Pagaralam City, South Sumatra Province, not only used people's plantation land, but also used protected forest areas for coffee farming. One of them is in the Community Forest (HKM), which is located in the Bukit Dingin protected forest area. The research objective was to determine the characteristics and economic achievements of coffee farmers in the HKM Bukit Dingin protected forest area in Agung Lawangan Village, Dempo Utara District, Pagaralam City. The research location was chosen purposively by condisering has the largest number and members of HKM and also the largest coffee area. The research method used is a survey method with probability sampling techniques, where 47 farmers are randomly selected as samples. The data analysis method used qualitative and quantitative descriptive analysis. The results showed that the average age of coffee farmers is at a productive age of 16-64 years with the level of education of most farmers still relatively low at the elementary education level. The number of family members of coffee farmers is included in small families with the number of family members 1-3 people and experience is included in the category of experience above 10 years. In addition, the area of ​​coffee farmers' land is dominated by medium land area of ​​0.5-2Ha. Meanwhile, the economic achievements of coffee farmers obtained from coffee farming in HKM Bukit Semantung amounted to Rp. 17,568,050.72 / Ha / Year higher than the achievements of farmers in HKM Kibuk Rp. 16,542,128.96 / Ha / Year and HKM Muara Siban Lestari Rp. 15,811,604.18 / Ha / Year.